Aluminyum alaşımlarının sürtünme kaynak özellikleri - Gürler, Mustafa (My University, 2000)
Friction welding is a solid-state welding process in which the heat for welding is produced by the relative motion of the two interfaces being joined. This method relies on the direct conversion of mechanical energy to thermal energy to form the weld, without the application of heat from any other source. Under normal conditions no melting occurs at the interface. Similar and dissimilar metals can be joined by this welding process. In this thesis friction weldability of wrought aluminium alloys and their mechanical properties were investigated. Aluminium-steel, aluminium-copper and aluminium-aluminum alloys were friction welded. The weldments were mechanically tested and metallographically examined. With the exception of Al-Al alloys, other welding trials gave poor results, because the welding machine used in welding was built for only steel weldments. Joining dissimilar aluminium alloys gave fair results. The metal lose in welding was closely examined in the tests. The following results were obtained from the experiments: 1. Aluminium-stell weldments need high rotational velocity. 2. Aluminium-aluminium welds can be achieved at a low rotational velocity 3. Metal lose in welding increases with friction forces and welding time 4. Mechanical properties of welded samples are poorer than unwelded samples.
Keywords: Alüminyum; Metaller